Factors Affecting Utilization of the E-Health “Seha” Interactive Application for Online Medical Consultation in Saudi Arabia - Al-Kahtani NK; Aljabri D; Alrawiai S; Alsubaie S; Alasmari M; Aldukhi Z; Alkahtani HK (Dove Medical Press, 2022)
Nouf Khalid Al-Kahtani,1 Duaa Aljabri,1 Sumaiah Alrawiai,1 Shayma Alsubaie,1 Maram Alasmari,1 Zahra Aldukhi,1 Hend Khalid Alkahtani2 1Health Information Management and Technology, College of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia; 2Department of Information Systems, College of Computer and Information Science, Princess Nourah bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Nouf Khalid Al-Kahtani, Department of Health Information Management and Technology, College of Public Health, Imam Abdulrahman Bin Faisal University, Dammam, 31441, Saudi Arabia, Email nkalkahtani@iau.edu.saPurpose: Telehealth, Internet interventions, or digital apps provide healthcare to isolated regions and can span borders. The purpose of this research was to assess the use of the Seha application, public perceptions toward the application, and factors that affect its utilization.Methods: The cross-sectional method was used to analyze the quantitative data. Grounded Theory was used to analyze the qualitative data. This study was conducted from December 1, 2018, to January 31, 2019. A total of 419 participants were surveyed online, and semi-structured interviews were conducted for 20 participants. The participants were chosen based on convenience sampling techniques. The survey contained two sections. The first section consisted of demographic data and the second section included eight questions, each covering one main aspect. For the qualitative approach, participants were chosen using a theoretical sampling technique. Researchers acted as the primary data collection instrument.Results: Out of the total, 88.5% of the participants did not use "Seha" application. Among users, the main perceived benefit from the application was the ability to contact a general practitioner anytime. Among non-users, the greatest barrier to use was the lack of awareness about it, while the ability to contact a general practitioner any time (25%) and reducing visits to the doctor (23%) were the top motivations. A conceptual framework was developed to define the different aspects affecting the use of the online medical consultation application. These aspects included awareness and education, technical issues, access, and consultation information.Conclusion: Public awareness and education about the application, as well as the integration of its functions with other healthcare systems were the main recommendations suggested. Implementing these recommendations is encouraged to deliver value to e-health initiatives in Saudi Arabia.Keywords: health care, telemedicine, mobile application, digital health, e-health